Legal Strength of Land Purchase and Sale in the Village of Banyuning, Buleleng - Pratama, Putu Rama Ari; Sujana, I Nyoman; Sukandia, I Nyoman (Protection: Journal Of Land And Environmental Law, 2026)
The ambiguity of the legal status of village residential land after the enactment of the Basic Agrarian Law, particularly concerning the transfer of land rights carried out through private sales transactions. This research uses an empirical legal research method with a juridical sociological, legislative, and conceptual approach. The data used consists of primary data obtained through interviews and secondary data collected from various related literature. The research results show that although the buying and selling transactions of village yard land in Banyuning are conducted without official registration at the land office, they are still recognized as valid by customary law as long as there is an agreement from the local customary community. However, under national law, these transactions are not valid as they do not meet the procedures established by land regulations. In conclusion, to provide clearer legal certainty, there needs to be regulations governing the authentic transfer of rights over village yard land through a Land Deed Official (PPAT) and registration at the land office.